Low-temperature thermochemical energy storage behavior of Zn-doped phosphogypsum-based calcium sulfate dihydrate: Correlating defect evolution with electronic structure - Fei Mu; Shuai Luo; Meng Fu; Yuanyuan Li; Xuyuan Tang; Yaoqi Huang; Xiaomin Cheng (Chemical Engineering Journal, 2026)

CuFe-LDH decorated ceramsite derived from industrial solid wastes for synergistic photo-Fenton degradation of phenol: Mechanistic insights into Cu/Fe redox cycling - QiYu; Xue-fei Lei; Chun-heng Wang; Yu Zhang; Wen-hao Zhang; Huan-huan Chen; Shao-hua Luo; Wen-ning Mu (Journal of Environmental Chemical Engineering, 2026)

Oral immunization of Nile tilapia with Chlorella-bioencapsulated multi-epitope fusion antigen effectively protects against Streptococcus agalactiae infection - Xiaodong Deng; Zichun Xiao; Dan Mu; Dianlong Xu; Juncai Li; Yuxuan Yang; Hanjie Gu; Yonghua Hu; Xiaowen Fei (Fish & Shellfish Immunology, 2026)

A synergistic antifungal buccal composite integrating Aureobasidin A and alkaline modulation for localized treatment of oral candidiasis - Jiaxin Yi; Li Xie; Xueping Shui; Xinzhi Tan; Yandong Mu; Wei Fei; Li Xiao; Weidong Tian; Jun Guo (Chemical Engineering Journal, 2026)

Advances in resource recovery technologies for retired wind turbine blades and high-value conversion into carbon materials - Xingyu Mu; Meitong Li; Lingyun Cao; Pengyao Liu; Yuqing Yue; Wenjiao Yuan; Xuening Fei (Journal of Environmental Chemical Engineering, 2026)

Orbital symmetry matching-mediated synergistic N2/CO2 activation on Cu-Co3O4 for photocatalytic urea synthesis - Meng Qiao; Yan-Fei Mu; Ji-Li Zhou; Su-Xian Yuan; Meng-Ran Zhang; Min Zhang; Tong-Bu Lu (Chemical Engineering Journal, 2026)

Aging-Related Changes in the Injury Response of the Peripheral Nervous System - Yue-Yan Cen; Mu-Yun Wang; Qin-Xuan Song; Xin-Lin Gao; Cheng Zhou; Chun-Jie Li; Fei Liu; Yan-Yan Zhang; Jie-Fei Shen (Neuroscience Bulletin, 2026)
Peripheral nerve injury (PNI) significantly impairs patients’ quality of life, with elderly individuals experiencing particularly severe consequences due to aging-related declines in neuronal injury response and repair capabilities. Processes of the generation and transmission of injury signals, axonal disruption, initiation of regeneration, and the elongation of regenerating axons, as well as the subsequent reinnervation by these axons, are all significantly influenced by aging. These alterations are closely associated with changes in mitochondrial function, neuronal transport systems, a persistent inflammatory milieu, and various microenvironmental non-neuronal cells. Therefore, this review synthesized the pivotal role of aging in the multifaceted regulation of the nervous system following PNI and highlighted promising molecular regulatory mechanisms in the signaling pathways. Furthermore, it identified critical areas for future research, including unresolved questions in age-associated injury responses, potential targets for pharmacological intervention, and emerging therapeutic strategies meriting consideration for research and development.

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

Two decades of methane budgets at the sub-national scale in China - Pengfei Zhao; Zhen Zhang; Guanghui Huang; Zhenxuan Wang; Josep G. Canadell; Philippe Ciais; Huilin Chen; Shengqian Chen; Jason Blake Cohen; Fan Dai; Peng Gong; Robert B. Jackson; et al. (Science Bulletin, 2026)

Preference-conditioned multi-objective reinforcement learning for train carriage environment control - Boyuan Mu; Chunjun Chen; Lingwei Fei; Yutao Xia; Ji Deng (Building and Environment, 2026)

Development and application of KASP molecular marker for accelerated breeding of low-acid Cerasus humilis cultivars - Xia-Yu Xing; Xiao-Yan Wang; Yue-Zhan Xiao; Hao-Nan Wang; Hou-Qiang Song; Ming Liu; Xiao-Peng Mu; Jian-Cheng Zhang; Lu-Ting Jia; Yu Gary Gao; Shuai Zhang; Peng-Fei Wang (Plant Cell Reports, 2026)

Spatiotemporal patterns of bacterial communities and their responses to environmental gradients in a river–reservoir system - Yuhai Zhuo; Nan Li; Bobo Liu; Jianwu Li; Anli Song; Hao Mu; Fei Zhang; Xiang Liu; Zhi Yang; Tinglin Huang; Hongxi Zheng (Antonie van Leeuwenhoek, 2026)

Hybrid energy system based on co-firing municipal sludge coupled with power generation: energy balance, carbon emissions, and thermo-economic analysis - Zhaolei Meng; Zongguo Wen; Xin Meng; Fan Fei; Yanfei Mu; Gang Li; Tao Zhou; Quanjie Li; Yiqun Meng (Journal of Cleaner Production, 2026)

Mixing and stratification dynamics shape bacterial community composition, assembly patterns, and co-occurrence networks in Han River cascade reservoirs - Hao Mu; Haihan Zhang; Jianwu Li; Anli Song; Bobo Liu; Yuhai Zhuo; Fei Zhang; Xiang Liu; Tinglin Huang; Nan Li; Hongxi Zheng (Environmental Research, 2026)

Antioxidant Enzyme Activities and Metabolic Responses of the Posterior Gills of Mud Crab (Scylla paramamosain) Under Long-Term Stress in Coastal Chloride-Dominated Low-Salt Saline-Alkali Water - Ziwei Fan; Kangxiang Qin; Fei Wang; Chenxi Che; Yuntao Li; Wenjun Li; Shan Gao; Chunlin Wang; Changkao Mu; Huan Wang (Journal of Ocean University of China, 2026)

A smartphone-controlled microfluidic platform for rapid, sample-to-answer HLA-B*58:01 genotyping via LNA-enhanced duplex RPA - Xinpei Pang; Zhubing Lei; Xiang Mu; Shuang Wu; Wen-Fei Dong; Qian Mei (Chemical Engineering Journal, 2026)

GPP dominates the change of WUE trend in the future period - Haili Dong; Fei Tian; Peiwen Mu (Theoretical and Applied Climatology, 2026)

Bayesian-Optimized Neural Networks with High-Fidelity FEM for Intelligent Residual Strength Prediction in Damaged Ships - Jianxiao Deng; Fei Peng; Jinlei Mu; Hailiang Hou (Journal of Marine Science and Engineering, 2026)
The rapid and accurate assessment of residual ultimate strength after ship damage is crucial for rescue decision-making and navigation safety, while traditional methods struggle to meet the demands of complex random damage scenarios in terms of efficiency or accuracy. This study proposes a hybrid framework that integrates high-fidelity nonlinear finite element simulation (NFEM) and a Bayesian-regularized backpropagation neural network (BPNN). NFEM is used to accurately simulate a large number of random damage scenarios, generating a physically credible benchmark dataset. BPNN serves as an efficient surrogate prediction model, with its key parameters—the number of hidden layers and the training algorithm—systematically optimized to enhance generalization capability. The results show that: (1) The NFEM simulation results deviate by less than 5% compared to the Smith method, validating the reliability of the dataset. (2) The prediction performance of BPNN is highly dependent on the number of hidden layers and the training algorithm, exhibiting non-monotonic variation, with an optimal parameter combination identified as 8 hidden layers paired with the Bayesian algorithm, achieving a prediction regression value R of 0.91662. (3) Deep networks are prone to overfitting, while shallow networks suffer from insufficient feature capture. (4) The Bayesian algorithm performs best in terms of overfitting resistance and stability. This study not only provides a high-precision and efficient intelligent solution for residual strength assessment of damaged hulls, but its systematic neural network parameter optimization strategy, particularly the approach of identifying optimal depth and selecting anti-overfitting algorithms, also offers an important reference for the design of intelligent damage assessment models for similar engineering structures.

Mitigating 2-MIB and odor-producing cyanobacteria in a shallow drinking-water reservoir using sponge‑iron-assisted water-lifting aeration - Fei Zhang; Rong Li; Hao mu; Yuhai Zhuo; Zhi Yang; Tinglin Huang; Nan Li (Journal of Water Process Engineering, 2026)

The fermentation characteristics of the milk fermented by the combined starter culture of Lactobacillus delbrueckii, Lacticaseibacillus paracasei, and Kluyveromyces marxianus - Liao Deng; Fei Gao; Baosheng Cui; Jiatong Yao; Fan Zhang; Guangqing Mu; Yanfeng Tuo (Food Bioscience, 2026)

Distribution and evolution of distress in embankment-bridge transition sections of the Gonghe–Yushu Expressway in degrading permafrost regions - Bingyan Li; Minghao Liu; Yanhu Mu; Jing Luo; Xin Ju; Fei Yin; Fan Yu; Yunhui Huang (Transportation Geotechnics, 2026)

Corrigendum to “Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus” [Fish Shellfish Immunol. 165 (2025) 110566] - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2026)

Metabolic adaptations in the hypothermic myocardium: Mechanisms and clinical implications - Huimin Wu; Fei Xiao; Yuan Zhang; Huili Li; Mu Jin; Peirong Lin; Fushan Xue; Sheng Wang (Cryobiology, 2026)

Production of carbon nanomaterials from industrial waste salts containing organic pollutants: Carbon quantum dots, graphene, and fullerenes - Pengyao Liu; Lan Li; Lingyun Cao; Xingyu Mu; Meitong Li; Xuening Fei (Journal of Environmental Chemical Engineering, 2026)

Effects of taurine on immunity and ammonia metabolism in large-scale loach under ammonia stress - Ruo-Yu Zhou; Lu Chen; Meng-Yang Hu; Mu-Xi Li; Yu-Xuan Fei; Mei Huang; Yun-Long Zhang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Bimetallic metal-organic frameworks with hydrolytic esterase activity applied to mycotoxin decontamination - Ke Cheng; Peiheng Dina; Fei Yu; Yinghui Zhang; Yunpeng Wang; Wenjing Mu; Xiuguo Wang (Chemical Engineering Journal, 2026)

FM-SAM: individual tree crown delineation and classification based on Segmentation Anything Model (SAM) and YOLOv10 in UAV imagery for forest monitoring - Haohua Que; Haojia Gao; Weihao Shan; Mingkai Liu; Jianshuo An; Fei Deng; Shuo Feng; Xinghua Yang; Lei Mu (Computers and Electronics in Agriculture, 2026)

Corrigendum to “Real-time cooperative multi-target tracking with low-cost radar in complex marine environments” [Ocean Eng. 345 (2026) 123694] - Fei Wang; Qingwang Han; Mu Lv; Rui Gao (Ocean Engineering, 2026)

Real-time cooperative multi-target tracking with low-cost radar in complex marine environments - Fei Wang; Qingwang Han; Mu Lv; Rui Gao (Ocean Engineering, 2026)

Multi-USV cooperative encirclement strategy based on the double-layer prioritized replay mechanism in the reef sea area - Dongdong Mu; Fei Wang; Xinjie Han; Xiao Liang; Guibing Zhu; Yunsheng Fan (Ocean Engineering, 2026)

Characterization of monoclonal antibody against IgM and phagocytic function of IgM+ B cells in snakehead (Channa argus) - Peng Fei Mu; Zhe Wang; Qi Li; Qiu Hua Li; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2026)

Discovery of novel nuciferine-based URAT1 inhibitors for hyperuricemia: synthesis, biological evaluation, and computational insights - Yan-fei Liu; Ze-sheng Hao; Xu Guo; Shu-tao Sun; Mu-xuan Wang; Meng-qi Zhang; Ying-ying Chen; Jin-yue Sun; Chao Liu (Medicinal Chemistry Research, 2026)

LCN2-positive alveolar type II cells promote silica-induced pulmonary fibrosis via STAT3-TGF-β1-Smad3-mediated signaling - Zihao Xie; Xia Li; Mengchen Zhang; Hangbing Cao; Fei Wang; Ruiqing Yan; HuiYu Ye; Min Mu; Jianxin Wang; Fei Wang; Xinrong Tao (Toxicology and Applied Pharmacology, 2025)

Ecological implications of biodegradable and conventional microplastics: Dissolved organic matter bioavailability and microbial response in marine systems - Yu-xin Wu; Hao-yu Wang; Wang-chao Chu; Yuan-yuan Gao; Mu-qiu Xia; Fei-fei Liu (Journal of Hazardous Materials, 2025)

Dual identification optical sensor for sodium benzoate and potassium sorbate based on UV-DAS combined with SEP-CNN-TL - Junfeng Wang; Rui Zhu; Jie Gao; Fei Xie; Mu Li; Changyin Li; Yungang Zhang; Hongbin Lin (Food Control, 2025)

Efficient radiocobalt removal from seawater and radioactive liquid waste using a radiation-stable layered metal sulfide ion exchanger - Fei Han; Aocheng Yuan; Zhi Zhang; Qingquan Deng; Jiaoting Li; Shuibo Wu; Mingdong Zhang; Jingli Mu (Desalination, 2025)

Water-induced distress characteristics and mechanism of a separated expressway traversing thaw-sensitive permafrost zones - Minghao Liu; Bingyan Li; Yanhu Mu; Jing Luo; Fei Yin; Xiangbing Kong (Cold Regions Science and Technology, 2025)

MicroRNA-451: A multifaceted regulator in cerebral and cardiac ischemia-reperfusion injury - from molecular mechanisms to therapeutic potential - Fei-xiang Wang; Zu-an Shi; Zi-hang Yu; Bin Lu; Guo Mu (Molecular Biology Reports, 2025)

TiO2-Doped Fe-Tailings Heterogeneous Catalysts: Engineering Synergistic Photocatalytic-Fenton Pathways for High-Efficiency Phenol Mineralization - Wen-hao Zhang; Yu Wei; Qi Yu; Chun-heng Wang; Xue-fei Lei; Shao-hua Luo; Huan-huan Chen; Wen-ning Mu (International Journal of Environmental Research, 2025)

Rhizobium rhizogenes-mediated genetic transformation for hairy root induction of Blumea balsamifera - Qiumei Luo; Sihong Sang; Minghui Huang; Kailang Mu; Fei Ran; Shan Sha; Changmao Guo; Jie Zou; Yuchen Liu; Yuxin Pang (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Hourly photosynthetically active radiation prediction in solar greenhouses using Bayesian optimized machine learning and deep learning based on limited local weather data - Menglong Wu; Ruoyu Li; Chang Lv; Aihong Dong; Fei Mu; Wenquan Niu (Computers and Electronics in Agriculture, 2025)

Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2025)

Spirulina-derived atomically dispersed Fe–N4 sites on g-C3N4 for efficient CO2 photoreduction - Haoxian Wang; Junjie Wang; Jin Xu; Jingkai Lin; Zhongshuai Zhu; Yazi Liu; Feihu Mu; Bin Huang; Fei Yu; Chenmin Xu; Shaogui Yang; Huan He; et al. (Chemical Engineering Journal, 2025)

Tissue-Selective Separation Mechanism of Multi-type Soft Tissues Under Waterjet Impact for Low-Trauma Cutting Surgery - Jiaqi Zhao; Xiao-Fei Song; Xiaoxian Wei; Jiuke Mu; Peng Peng; Wenli Yu (Annals of Biomedical Engineering, 2025)

Epithelial cells facilitate tissue fibrosis through early growth response-1 overexpression in IgG4-related disease - Ruijie Sun; Qinhuan Luo; Mu Wang; Linyi Peng; Wei Wei; Yanmei Li; Jiaxin Zhou; Yuxue Nie; Jingna Li; Qing Zhong; Yunyun Fei; Mengtao Li; et al. (Science Bulletin, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Beyond Paradox: Ozone Therapy as a Hormetic Modulator in Ischemia-Reperfusion Injury - An Update - Yong Ye; Zi-hang Yu; Liang Nie; Fei-xiang Wang; Guo Mu (Cell Biochemistry and Biophysics, 2025)

Activation of NR2A-Wnt-TLR2 Signaling Axis in Satellite Glial Cells of the Dorsal Root Ganglion Contributes to Neuropathic Pain Induced by Nerve Injury in Diabetic Mice - Yan-Yan Zhang; De-Xin Zhu; Mu-Yun Wang; Ya-Ting Yi; Yu-Heng Feng; Cheng Zhou; Chun-Jie Li; Fei Liu; Jie-Fei Shen (Molecular Neurobiology, 2025)

Constructing sodium L-aspartate assisted N-doped carbon encapsulated hollow CoP spheres with enhanced electrochemical kinetics and its derived macroporous N-doped carbon foam for high-energy density hybrid supercapacitors - Xiaolin Liu; Tian Tian; Aifeng Liu; Zengcai Guo; Jingbo Mu; Xiaoliang Zhang; Xuan Yue; Xiaoyan Liu; Fei Gao; Hongwei Che (Chemical Engineering Journal, 2025)

Heat Deficit for Vegetation Leaf Senescence and Its Key Accumulation Process and Determinants at Northern Middle and High Latitudes During 2001–2022 - Zhihui Yuan; Gang Bao; Fei Li; Jiquan Chen; Jingfeng Xiao; Qier Mu; Enliang Guo; Siqin Tong; Sainbuyan Bayarsaikhan (Global Ecology and Biogeography, 2025)
Aim Cold degree days (CDD) represent the heat deficit for vegetation leaf senescence in autumn and serve as a critical parameter in modelling leaf senescence. This study aimed to quantify the spatiotemporal patterns of CDD and its key accumulation processes and determinants. Location At northern middle and high latitudes (> 30° N). Period 2001–2022. Major Taxa Studied Vegetation. Methods We estimate CDD as the cumulative sum of the difference between the daily mean temperature and a threshold temperature (12.75°C) during the period from midsummer to the end of the growing season. To identify its crucial metric, we employ a combination of grey relational analysis, random forest model and partial correlation analysis. Results The average CDD increases linearly with latitude at a rate of 5.9°C‐days per degree. Higher latitudes exhibit larger CDD (> 300.0°C‐days), longer accumulation periods (> 70 days) and faster accumulation rates (> 6.0°C/day), whereas lower latitudes show smaller CDD ( 46% of the study area, especially at high latitudes and on the Tibetan Plateau. While climate warming generally reduces CDD, an increase in precipitation frequency can counteract this trend and shape the relationship between precipitation amount and CDD. The effects of radiation and wind speed on CDD were less pronounced than those of precipitation frequency, with wind exerting a positive (cooling) effect that increases CDD accumulation and radiation producing a negative (heating) effect that decreases CDD accumulation. Main Conclusions This study highlights the critical aspects of the CDD accumulation process and emphasises the importance of incorporating precipitation frequency into CDD‐based autumn phenology models across northern latitudes.

Distinguishing the botanical origins of rare honey through untargeted metabolomics and machine learning interpreting flavonoid profiles - Sha Yan; Yuzhe Yuan; Fei Pan; Guodong Mu; Haitao Xu; Xiaofeng Xue (Food Chemistry, 2025)

Chitosan and gelatin based sprayable hydrogels incorporating photothermal and long-acting antibiotic sterilization for infected wound management with shape adaptability - Fei Wang; Xing Wang; Siwei Li; Qisen Yang; Haibo Mu; Jinyao Li; Yu Yang (Carbohydrate Polymers, 2025)

Removal and ecological impact of sulfamethoxazole and N-acetyl sulfamethoxazole in mesocosmic wetlands dominated by submerged plants: Plant tolerance, microbial response, and nitrogen transformation - Xiaoying Mu; Congli Chen; Qinya Fan; Weihang Zhang; Fei Liu; Jiaxun Guo; Weixiao Qi; Huijuan Liu (Science of The Total Environment, 2025)

Lignite degraded by Trichoderma citrinoviride: Products, processes and mechanisms - Xingyu Mu; Meitong Li; Jianhua Tian; Wenjiao Yuan; Hui Shen; Ruijie Zhang; Shuwei Li; Xin Feng; Xuening Fei; Yuhong Xie (International Biodeterioration & Biodegradation, 2025)

Numerical Simulation Analysis of an Offshore Multi-Row Arrangement Longline Aquaculture Facility with Lantern Nets Under Environmental Loads - Yingna Mu; Guoxuan Liang; Changping Chen; Ruitong Zhang; Fei Teng; Yanbin Tan (Fishes, 2024)
The structural hydrodynamic response of longline aquaculture facilities under the influence of waves and currents is complex. Studying the hydrodynamic characteristics of this aquaculture structure in complex sea environments can contribute to sustainable offshore aquaculture solutions. Thus, we established a numerical model using AquaSim2.18, a proven and effective finite element hydrodynamic software for analyzing the maximum tension in mooring lines and main lines, the displacement of the main lines, and the forces on the lantern nets under waves and currents. The results showed that positioning the system in the direction of incidence of waves and currents minimizes tension in both mooring and main lines, making a downstream arrangement optimal; compared with a single row, the maximum reduction in the tension of the mooring lines is 3.3% and 1.8% for five-row and row-row lines, respectively, and the shadow effects reduced the downstream mooring force. Additionally, line tension increased with wave height and current velocity, whereas wave periods had variable effects due to the period range; the lantern net forces increased with wave height and decreased with wave period. Wave height was also shown to influence the horizontal displacement of main lines. The findings can provide a reference for the hydrodynamic characteristics of different components of the structure.

Regionally adapted conservation tillage reduces the risk of crop yield losses: A global meta-analysis - Jun Sun; Wenquan Niu; Yadan Du; Li Ma; Siying Huang; Fei Mu; Qian Zhang; Guochun Li; Jinjin Zhu; Kadambot H.M. Siddique (Soil and Tillage Research, 2024)

Research on the pitch angle attitude control of underwater vehicles based on a novel butterfly-shaped blocks structure - Yanhu Chen; Xinyu Fei; Xiutong Mu; Xiaoyan Zhao; Suohang Zhang; Canjun Yang (Ocean Engineering, 2024)

Detection of ultra-low concentration NH3, SO2, and NO using UV-DOAS combined with multidimensional spectral fusion - Fei Xie; Yongqi Wu; Jie Gao; Mu Li; Rui Zhu; Xijun Wu; Yungang Zhang (Fuel, 2024)

Exposure to environmentally relevant levels of GenX affects placental and offspring development in mice - Yuhan Dai; Junlin He; Fei He; Zhuxiu Chen; Yu Jiang; Yanqing Geng; Jianwei Geng; Yongrui Zhou; Xuemei Chen; Fangfang Li; Yingxiong Wang; Xinyi Mu (Environmental Pollution, 2024)

Microbial transformation of lignite into methane: Insights from anaerobic-activated sludge systems - Ruijie Zhang; Meitong Li; Wenjiao Yuan; Xin Feng; Xuening Fei; Xingcheng Zhao; Gangzhen Jiao; Hui Shen; Xingyu Mu; Yuhong Xie (Bioresource Technology Reports, 2024)

Global path planning for Unmanned Surface Vehicles in complex maritime environments considering environmental interference - Dongdong Mu; Tanghui Li; Xinjie Han; Yunsheng Fan; Fei Wang (Ocean Engineering, 2024)

Asymmetric impact of ENSO on the late winter Warm Arctic-Cold Eurasian pattern - Gaoyuan Mu; Wenjun Zhang; Feng Jiang; Dingzhu Hu; Fei-Fei Jin (Climate Dynamics, 2024)

Synthesis of Iron-Tailing-Based porous ceramic granules for the adsorption of phenol-containing wastewater degradation - Yu Wei; Xue-fei Lei; Shao-hua Luo; Huan-huan Chen; Wen-ning Mu; Fei Teng; Kuo Sun; Shengxue Yan (Journal of Cleaner Production, 2024)

Unraveling the chemosensory attributes of braised beef prepared from different regions using GC-MS combined with multivariate data analysis - Jie Sun; Mingyu Li; Xiaoqing Mu; Li Chen; Dequan Zhang; Fei Fang; Xiaoying Niu; Chunjiang Zhang (International Journal of Gastronomy and Food Science, 2024)

Dimeric piperidinoquinoline alkaloids from the seeds of Chimonanthus salicifolius - Zhan-Peng Yu; Yu-Xia Wang; Li-Hong Hong; Ya-Lin Li; Jian-Fei Zhang; Mu Li; Ping Ying; Qiang Zheng; Ling-Yi Kong; Jian-Guang Luo (Phytochemistry Letters, 2024)

Vegetation factors and atmospheric dryness regulate the dynamics of ecosystem water use efficiency in a temperate semiarid shrubland - Yanmei Mu; Xin Jia; Ziqi Ye; Xulin Guo; Shaorong Hao; Tianshan Zha; Yuqing Zhang; Cong Han; Shengjie Gao; Fei Xing; Shugao Qin; Peng Liu; et al. (Journal of Hydrology, 2024)

SIRT1-Mediated HMGB1 Deacetylation Suppresses Neutrophil Extracellular Traps Related to Blood–Brain Barrier Impairment After Cerebral Venous Thrombosis - Shuwen Mu; Ziqi Li; Long Lin; Di Wang; Fei Yang; Li Chen; Liang Xian; Kunzhe Lin; Yinghong Lin; Dan Ye; Yang Yang; Liangfeng Wei; et al. (Molecular Neurobiology, 2024)

The construction of Cs3MoxSbyBr9/BiVO4 S-scheme heterojunction photocatalyst for efficient photocatalytic N2 fixation - Zhao-Lei Liu; Han-Ying Luo; Meng-Ran Zhang; Yan-Fei Mu; Fu-Quan Bai; Min Zhang; Tong-Bu Lu (Chemical Engineering Journal, 2024)

Optimized tillage can enhance crop tolerance to extreme weather events: Evidence from field experiments and meta-analysis - Jun Sun; Wenquan Niu; Fei Mu; Ruoyu Li; Yadan Du; Li Ma; Qian Zhang; Guochun Li; Jinjin Zhu; Kadambot H.M. Siddique (Soil and Tillage Research, 2024)

Late gestational exposure to fenvalerate impacts ovarian reserve in neonatal mice via YTHDF2-mediated P-body assembly - Fei He; Xinyi Mu; Yan Zhang; Yongheng Wang; Jianwei Geng; Yanqing Geng; Yidan Ma; Xin Yin; Rufei Gao; Xuemei Chen; Junlin He (Science of The Total Environment, 2024)

Member separation and deformation recognition of spatial grid structures in-service - Mu-Nan Xu; Li-Min Sun; Yu-Fei Liu; Bao-Luo Li; Meng Zhou; Xuan Chen (Engineering Structures, 2024)

High organic aerosol in the low layer over a rural site in the North China Plain (NCP): Observations based on large tethered balloon - Jiannong Quan; Juntao Huo; Chenglong Zhang; Yubing Pan; Pengkun Ma; Zhiheng Liao; Zhigang Cheng; Xingcan Jia; Qianqian Wang; Qingyan Fu; Yujing Mu; Fei Hu (Science of The Total Environment, 2024)

Revealing the release and migration mechanism of heavy metals in typical carbonate tailings, East China - Rong Zhao; Xiong Wu; Ge Zhu; Xiao Zhang; Fei Liu; Wenping Mu (Journal of Hazardous Materials, 2024)

Cellular localization and potential ligands of a novel scavenger receptor class B/CD36 protein homolog (Pt-SRB2) identified in the marine crab, Portunus trituberculatus - Su-Ming Zhou; Fang-Mei Lin; Chang-Kao Mu; Chun-Lin Wang; Qi-Cun Zhou; Peng Sun; Fei Yin (Fish & Shellfish Immunology, 2024)

Modeling the effects of land use/land cover changes on river runoff using SWAT models: A case study of the Danjiang River source area, China - Weichao Liu; Jianhua Wu; Fei Xu; Dawei Mu; Pengbin Zhang (Environmental Research, 2024)

Identification of the Spatiotemporal Variability and Pollution Sources for Potential Pollutants of the Malian River Water in Northwest China Using the PCA-APCS-MLR Receptor Model - Dawei Mu; Jianhua Wu; Xiaofei Li; Fei Xu; Yongqiang Yang (Exposure and Health, 2024)

Establishment of CRISPR-Cas-based antiparasitic agents for the swimming crab parasite Mesanophrys sp. - Xiaopeng Wang; Yueyue Zhou; Yingchao Zhang; Xiaofen Song; Ce Shi; Yuanyuan Fu; Lei Liu; Changkao Mu; Fei Yin; Weiwei Song; Chunlin Wang (Aquaculture, 2024)

A novel Vibrio alginolyticus phage and its therapy application in Portunus trituberculatus larvae - Ruqian Cai; Dengfeng Li; Weinan Qin; Wei Lin; Lingting Pan; Minhua Qian; Fei Wang; Chunlin Wang; Changkao Mu; Yigang Tong (Aquaculture, 2024)

Groundwater Quality Assessment Using EWQI With Updated Water Quality Classification Criteria: A Case Study in and Around Zhouzhi County, Guanzhong Basin (China) - Yongqiang Yang; Peiyue Li; Vetrimurugan Elumalai; Jing Ning; Fei Xu; Dawei Mu (Exposure and Health, 2023)

Nitrogen limitation affects carbon and nitrogen metabolism in mung bean (Vigna radiata L.) - Hang Zhou; Ya Liu; Baomin Mu; Fei Wang; Naijie Feng; Dianfeng Zheng (Journal of Plant Physiology, 2023)

Effect of oxyresveratrol on the quality and membrane lipid metabolism of shiitake mushroom (Lentinus edodes) during storage - Ben Niu; Yingchang Fei; Ruiling Liu; Hangjun Chen; Xiangjun Fang; Weijie Wu; Honglei Mu; Haiyan Gao (Food Chemistry, 2023)

Cumulative health risk in children and adolescents exposed to bis(2-ethylhexyl) phthalate (DEHP) - Xiangyun Gao; Liang Cui; Yingming Mu; Ji Li; Zhichao Zhang; Haiya Zhang; Fei Xing; Liang Duan; Jiaqi Yang (Environmental Research, 2023)

Regime Shifts in the Damage Caused by Tropical Cyclones in the Guangdong–Hong Kong–Macao Greater Bay Area of China - Manli Zheng; Lin Mu; Wenjuan Li; Fei Wang; Yan Li (Journal of Marine Science and Engineering, 2023)
Tropical cyclones (TCs) pose a significant threat in terms of wind-induced damage and storm risk to the Guangdong–Hong Kong–Macao Greater Bay Area (GBA) of China. In this research, annual power dissipation index (PDI) and storm surge and wave destructive potential (SDP) index from June to November were used to estimate the damage caused by the TC events in the buffer zone of the GBA. The regime shifts in 1993 and 2013 were identified through the Bayesian changepoint detection in six TC datasets. The TC-induced damage during 1994–2012 (the low-damage period) was weaker than that in 1977–1993 and 2013–2020 (the high-damage periods). The intensity and size of stronger TCs are the dominant factors responsible for the interdecadal changes in the TC damage. This may be explained by the influences of sea surface temperature (SST), surface latent heat flux and mid-level relative humidity. During high-damage periods, TCs can extract more energy from the ocean, leading to increased TC intensity and larger size. Conversely, during low-damage periods, TCs undergo a decrease in energy intake, resulting in reduced TC power and smaller size. The variations in the SST are relative to the Luzon Strait transport. In addition, the reduction in TC translation speed is unfavorable for the development of TCs in low-damage periods. Further research suggested that mid-level steering flow affects the TC movement velocity. The results offer valuable insights into the variations in the TC-induced damage in the GBA.

Molecular mechanism by which StSN2 overexpression inhibits the enzymatic browning of potato - Li-qin Li; Yu-lu Mu; Jing Chen; Qiang Wang; Yi-fei Lu; Sun Xin; Shi-min Yang; Xue-li Huang; Xi-yao Wang; Li-ming Lu (Postharvest Biology and Technology, 2023)

Isolation and characterization of tumorigenic bacteria associated with crown gall disease of Prunus humilis Bunge in China - Rong Xiao; Xiao-Peng Mu; Jian-Cheng Zhang; Shuai Zhang; Chun-Fen Zhang; Shu Deng; Jun-Jie Du; Peng-Fei Wang (European Journal of Plant Pathology, 2023)

Underlying mechanisms for natural organic matters mediated aerobic ciprofloxacin transformation by sulfide - Han-Qing Zhao; Peili Lu; Fei Chen; Hongcheng Bai; Chen-Xuan Li; Guan-Nan Zhou; Jing Wang; Lilan Zhang; Yang Mu (Journal of Environmental Chemical Engineering, 2023)

Size-controllable Rh2P nanoparticles on reduced graphene oxide toward highly hydrogen production - Hongqiang Xin; Lan Sun; Yiwei Zhao; Yuanjiang Lv; Qiaomei Luo; Shengwu Guo; Danyang Li; Ce Mu; Bo Huang; Fei Ma (Chemical Engineering Journal, 2023)

Dynamic Distribution of Mesanophrys sp. and Tissue Enzyme Activities in Experimentally Infected Mud Crab Scylla paramamosain - Kexin Zhang; Weiren Zhang; Ronghua Li; Junkai Lu; Qingwei Chen; Haojie Hu; Fei Yin; Changkao Mu; Weiwei Song; Chunlin Wang (Fishes, 2023)
Mesanophrys sp. is reported to be highly pathogenic to marine crustaceans. This study presents the first report of Mesanophrys sp. infection in the mud crab (Scylla paramamosain). In this study, we first recorded the survival rates of an experimentally infected group and a control group; the cumulative survival rate in the infected group was significantly lower compared to the control group after 72 h (73.20% vs. 94.19%), while the highest mortality of S. paramamosain occurred within the first 24 h post-infection. Then, we investigated the dynamic distribution and tissue tropism of the Mesanophrys sp. in the infected S. paramamosain by a quantitative real-time polymerase chain reaction (qPCR). The result showed that a significant increase in the number of Mesanophrys sp. could be detected in all tested tissues (obtained from the eyestalks, gills, heart, nerves, muscles and hepatopancreas) at 3 h post-infection. The numbers of Mesanophrys sp. in the gill, eyestalk and nerve tissues were relatively higher than in the other tissues. The gill tissue showed the highest numbers from 6 to 48 h. Histopathological observation found a severe collapse in the filament structure, which indicated tissue-specific pathogen infection. Furthermore, the antioxidant enzyme activity of superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD) in three representative tissues (gill, muscle and hepatopancreas) were compared between the infected and control groups, and a significant increase in enzyme activity was observed in all three tested tissues in the infected group, indicating a relatively strong innate immune defense reaction that could have been induced by Mesanophrys sp. infection. These results will be helpful to Mesanophrys sp. pathogenicity-related research and the control of this pathogen in S. Paramamosain in the future.

Dependence assessment in human reliability analysis using the 2-tuple linguistic information and DEMATEL method - Fei Gao; Wenjiang Liu; Xu Mu; Wenhao Bi; An Zhang (Process Safety and Environmental Protection, 2023)

Impact of Climate Change on Water Transfer Scale of Inter-basin Water Diversion Project - Tao Bai; Lei Li; Peng-fei Mu; Bao-zhu Pan; Jin Liu (Water Resources Management, 2023)

Applicability analysis of thermosyphon for thermally stabilizing pipeline foundation permafrost and its layout optimization - Fei Wang; Guoyu Li; Fedorov Alexander; Wei Ma; Dun Chen; Gang Wu; Yanhu Mu; Xinbin Wang; Hongyuan Jing; Zhenrong Zhang (Cold Regions Science and Technology, 2023)

Assessment of permafrost disturbances caused by two parallel buried warm-oil pipelines: A case study at a high-latitude wetland site in Northeast China - Fei Wang; Guoyu Li; Wei Ma; Dun Chen; Gang Wu; Yapeng Cao; Yanhu Mu; Yuncheng Mao; Jun Zhang; Kai Gao; Xinbin Wang; Hongyuan Jing; et al. (Cold Regions Science and Technology, 2023)

Biogenetic peloidal micrites within coral skeletons cause geochemical anomalies in reef limestones, Zhongsha Atoll, South China Sea - Hong-Qiang Yang; Xi-Yang Zhang; Yue Li; Qi Shi; Shi-Chen Tao; Xi-Nan Mu; Ming-Zhuang Wang; Xiao-Ju Liu; Fei Tan; Sheng-Nan Zhou; Guan Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Two new alkaloids from Tibetan medicine of Hypecoum leptocarpum - Bo Sun; Israa Assani; Chun-Gu Wang; Mu-Xuan Wang; Ling-Fei Liu; Yan Li; Ge Yan; Yun-Ruo Yang; Zhi Chen; Zhi-Xin Liao (Natural Product Research, 2022)

Linkages among the functional traits, insect visitation rate and seed set of Gentiana taxa on the Tibetan Plateau - Wen-fei Dai; Rui Gao; Meng-ying He; Yu-lian Yang; Fang-lan Li; Jun-peng Mu (Journal of Mountain Science, 2022)

Stability evaluation for steep bank slope with microseismic monitoring in Three Gorges Reservoir area - Qing-ming Xie; Kui Long; Zi-mu Li; Li-chuan Chen; Hong Liu; Hong Xu; Fei He; Dan Liang; Xue-kun Xiang; Qiang Ma (Journal of Mountain Science, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Preface to the Special Issue on Extreme Cold Events from East Asia to North America in Winter 2020/21 - Mu Mu; Dehai Luo; Fei Zheng (Advances in Atmospheric Sciences, 2022)

Delineating the Decussating Dentato-rubro-thalamic Tract and Its Connections in Humans Using Diffusion Spectrum Imaging Techniques - Si-Qi Ou; Peng-Hu Wei; Xiao-Tong Fan; Yi-He Wang; Fei Meng; Mu-Yang Li; Yong-Zhi Shan; Guo-Guang Zhao (The Cerebellum, 2022)

The regulation of the small-conductance calcium-activated potassium current and the mechanisms of sex dimorphism in J wave syndrome - Mu Chen; Yudong Fei; Tai-Zhong Chen; Yi-Gang Li; Peng-Sheng Chen (Pflügers Archiv - European Journal of Physiology, 2021)

Isolation and molecular characterization of bovine herpesvirus 4 from cattle in mainland China - Jun Lin; Rui-Hong Chen; Mu-Jiao Yang; Yuan-Mao Zhu; Fei Xue (Archives of Virology, 2021)

Evaluation of Arctic Sea-ice Cover and Thickness Simulated by MITgcm - Fei Zheng; Yue Sun; Qinghua Yang; Longjiang Mu (Advances in Atmospheric Sciences, 2021)

Use of QSAR and SSD methods on deriving predicted no-effect concentrations in seawater and sediment for ten individual parent- and alkyl-PAHs and a case study on the assessment of their ecological risks from the Dalian Bay, China - Ying Wang; Xing Liu; Yi Cong; Jin Fei; Juying Wang; Dian Zhang; Liang Liu; Jingli Mu; Ziwei Yao (Acta Oceanologica Sinica, 2020)

MiR-34a suppresses osteoblast differentiation through glycolysis inhibition by targeting lactate dehydrogenase-A (LDHA) - Mu Hong; Xiao-Bin Zhang; Fei Xiang; Xu Fei; Xue-Lian Ouyang; Xiao-Chun Peng (In Vitro Cellular & Developmental Biology - Animal, 2020)

The Activation of Heat-Shock Protein After Copper(II) and/or Arsenic(III)-Induced Imbalance of Homeostasis, Inflammatory Response in Chicken Rectum - Xin Yang; Hongjing Zhao; Yu Wang; Juanjuan Liu; Menghao Guo; Dongxue Fei; Mengyao Mu; Mingwei Xing (Biological Trace Element Research, 2020)

Elemental imbalance elicited by arsenic and copper exposures leads to oxidative stress and immunotoxicity in chicken gizzard, activating the protective effects of heat shock proteins - Menghao Guo; Hongjing Zhao; Yu Wang; Juanjuan Liu; Dongxue Fei; Xin Yang; Mengyao Mu; Mingwei Xing (Environmental Science and Pollution Research, 2019)

Engineering properties of loess stabilized by a type of eco-material, calcium lignosulfonate - Guo-yu Li; Xin Hou; Yan-hu Mu; Wei Ma; Fei Wang; Yu Zhou; Yun-cheng Mao (Arabian Journal of Geosciences, 2019)

More realistic land‐use and vegetation parameters in a regional climate model reduce model biases over China - Jiaojiao Gou; Fei Wang; Kai Jin; Xingmin Mu; Deliang Chen (International Journal of Climatology, 2019)
Accurate vegetation cover data are important for realistic simulation of regional climate. The default vegetation parameters from Global Land Cover 2000, currently incorporated into global climate models and used in regional climate model RegCM, are not realistic for China, which may have contributed to serious bias in surface climate simulation. In this study, a new set of vegetation parameters considering the Plant Functional Type (PFT) fractions and the corresponding monthly leaf area index (PFT_LAI), were developed based on the land cover and MODIS LAI data sets. The regional climate model RegCM4.5 coupled with the land surface model CLM4.5 were utilized to test the performance of the new vegetation parameters by comparing simulations with observations using different surface parameters. The surface energy balance was analysed to examine the effects of changed vegetation parameters on regional climate. The results showed that the new parameters were more accurate than the GLC2000 parameters when describing the distribution of crops, grassland, and forests over China. The improved vegetation parameters reduced model biases for winter air temperature and precipitation over southern China by 0.9°C and 8%, respectively, and reduced the winter temperature and summer precipitation biases over northeastern China by approximately 0.7°C and 8%, respectively. More accurate surface albedo are the main reasons for reductions in model bias. However, certain biases, such as the cold and dry bias over the Tibetan Plateau, still remained in the simulation results using our new vegetation data.

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

Permafrost warming along the Mo’he-Jiagedaqi section of the China-Russia crude oil pipeline - Fei Wang; Guo-yu Li; Wei Ma; Yun-cheng Mao; Yan-hu Mu; Mihaela Serban; Yong-jun Cai (Journal of Mountain Science, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Efficiency of sequential UV/H2O2 and biofilm process for the treatment of secondary effluent - Peng-Fei Yan; Shoujun Yuan; Wei Wang; Zhen-Hu Hu; Yang Mu; Han-Qing Yu (Environmental Science and Pollution Research, 2019)

Base cation concentrations in forest litter and topsoil have different responses to climate and tree species along elevational gradients - Feng Xue; Ming-fei Zhao; Yu-hang Wang; Mu-yi Kang; Kai-xiong Xing; Guo-yi Wang; Jing-jing Shi; Chen Chen; Yuan Jiang (Journal of Mountain Science, 2019)

Planetary scale selection of the Madden–Julian Oscillation in an air-sea coupled dynamic moisture model - Yuntao Wei; Fei Liu; Mu Mu; Hong-Li Ren (Climate Dynamics, 2018)

Cadmium and lead accumulations and agronomic quality of a newly bred pollution-safe cultivar (PSC) of water spinach - Ying-Ying Huang; Yang-Xiu Mu; Chun-Tao He; Hui-Ling Fu; Xue-Song Wang; Fei-Yue Gong; Zhong-Yi Yang (Environmental Science and Pollution Research, 2018)

Sensitivity of Colletotrichum acutatum to six fungicides and reduction in incidence and severity of chili anthracnose using pyraclostrobin - Yang-Yang Gao; Li-Fei He; Bei-Xing Li; Wei Mu; Jin Lin; Feng Liu (Australasian Plant Pathology, 2017)

Variations in soil moisture over the ‘Huang-Huai-Hai Plain’ in China due to temperature change using the CNOP-P method and outputs from CMIP5 - GuoDong Sun; Fei Peng; Mu Mu (Science China Earth Sciences, 2017)

Human activity and climate variability impacts on sediment discharge and runoff in the Yellow River of China - Yi He; Fei Wang; Xingmin Mu; Lanqin Guo; Peng Gao; Guangju Zhao (Theoretical and Applied Climatology, 2017)

Changes in daily and monthly rainfall in the Middle Yellow River, China - Yi He; Peng Tian; Xingmin Mu; Peng Gao; Guangju Zhao; Fei Wang; Pengfei Li (Theoretical and Applied Climatology, 2017)

The potential of fludioxonil for anthracnose control on China chili fruit - Yang-Yang Gao; Li-Fei He; Bei-Xing Li; Wei Mu; Jin Lin; Feng Liu (Phytoparasitica, 2017)

Investigation on prenatal dengue infections in a dengue outbreak in Guangzhou City, China - Jie Yang; Jiawen Zhang; Qundi Deng; Junping Wang; Yunbin Chen; Xiaohong Liu; Fei Wu; Jianmin Niu; Xiaoping Mu (Infectious Diseases, 2017)

Erratum to: Diurnal and seasonal variation of the elevation gradient of air temperature in the northern flank of the western Qinling Mountain range, China - Guo-yi Wang; Ming-fei Zhao; Mu-yi Kang; Kai-xiong Xing; Yu-hang Wang; Feng Xue; Chen Chen (Journal of Mountain Science, 2017)

Effects of freeze-thaw cycle on engineering properties of loess used as road fills in seasonally frozen ground regions, North China - Guo-yu Li; Wei Ma; Yan-hu Mu; Fei Wang; Shan-zhi Fan; Ya-hu Wu (Journal of Mountain Science, 2017)

CNOP-based sensitive areas identification for tropical cyclone adaptive observations with PCAGA method - Lin-Lin Zhang; Shi-Jin Yuan; Bin Mu; Fei-Fan Zhou (Asia-Pacific Journal of Atmospheric Sciences, 2017)

Diurnal and seasonal variation of the elevation gradient of air temperature in the northern flank of the western Qinling Mountain range, China - Guo-yi Wang; Ming-fei Zhao; Mu-yi Kang; Kai-xiong Xing; Yu-hang Wang; Feng Xue; Chen Chen (Journal of Mountain Science, 2017)

Thermal and spectral characterization of anaerobic thermal behavior patterns in a lacustrine sediment core - Fei Guo; Yunsong Mu; Cheng Chen; Haiqing Liao; Yingchen Bai (Environmental Science and Pollution Research, 2016)

The effects of CYP1A inhibition on alkyl-phenanthrene metabolism and embryotoxicity in marine medaka (Oryzias melastigma) - Jingli Mu; Fei Jin; Juying Wang; Ying Wang; Yi Cong (Environmental Science and Pollution Research, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Molecular characterization of Beclin 1 in rare minnow (Gobiocypris rarus) and its expression after waterborne cadmium exposure - Xiao-Hong Liu; Zhi-Jian Wang; Dong-Ming Chen; Mu-Fei Chen; Xing-Xing Jin; Jing Huang; Yao-Guang Zhang (Fish Physiology and Biochemistry, 2016)

Assessment of urban effect on observed warming trends during 1955–2012 over China: a case of 45 cities - Kai Jin; Fei Wang; Deliang Chen; Qiao Jiao; Lei Xia; Luuk Fleskens; Xingmin Mu (Climatic Change, 2015)

Water use efficiency of net primary production in global terrestrial ecosystems - Lei Xia; Fei Wang; Xingmin Mu; Kai Jin; Wenyi Sun; Peng Gao; Guangju Zhao (Journal of Earth System Science, 2015)

Vimentin Regulates Neuroplasticity in Transected Spinal Cord Rats Associated with micRNA138 - Bao-Jiang Qian; Ling You; Fei-Fei Shang; Jia Liu; Ping Dai; Na Lin; Mu He; Ran Liu; Yuan Zhang; Yang Xu; Yun-Hui Zhang; Ting-Hua Wang (Molecular Neurobiology, 2015)

An Informetric Profile of Water Resources Management Literatures - Jun-Lin Ren; Peng-Hui Lyu; Xin-Mu Wu; Fei-Cheng Ma; Zhi-Zhang Wang; Gang Yang (Water Resources Management, 2013)

Synthesis of novel isoquinolinone and 1,2-dihydroisoquinoline scaffolds via Ugi reaction and ring opening reaction of furans - Fei Ji; Wen-bin Yi; Mu Sun; Mei-fang Lv; Chun Cai (Molecular Diversity, 2013)

MiR-26a regulates cell cycle and anoikis of human esophageal adenocarcinoma cells through Rb1-E2F1 signaling pathway - Ya-Fei Zhang; An-Ran Zhang; Bi-Cheng Zhang; Zhi-Guo Rao; Jian-Fei Gao; Mu-Han Lv; Yu-Yun Wu; Su-Min Wang; Rong-Quan Wang; Dian-Chun Fang (Molecular Biology Reports, 2013)

Complete nucleotide sequence of a Chinese isolate of Grapevine leafroll-associated virus 3 reveals a 5′ UTR of 802 nucleotides - Fei Fei; Mu-Di Lyu; Jie Li; Zai-Feng Fan; Yu-Qin Cheng (Virus Genes, 2013)

Effects of 1,1,1-trichloroethane on enzymatic activity and bacterial community in anaerobic microcosm form sequencing batch reactors - Hui Li; Wei Zhang; Lu Li; Yong-Di Liu; Kuang-Fei Lin; Shu-Guang Lu; Bo-Zhong Mu; Xiao-Ming Du; Qiang Lu; Qian Zhang; Ting-Ting Shen; Bing-Zhi Li; et al. (Ecotoxicology, 2012)

Polyclonal rabbit anti-murine plasmacytoma cell globulins induce myeloma cells apoptosis and inhibit tumour growth in mice - Bo Mu; Jin-liang Yang; Lan-tu Gou; Yu-qin Yao; Yan Zhou; Zhi-hui Cheng; Hua-shan Shi; Zhi-yong Li; Yuan Wen; Fei Leng; Feng-yu Cui; Tian-tai Ma; et al. (Apoptosis, 2011)

Reproductive failure in wild boars associated to porcine parvovirus infection and in vivo and in vitro characterization of the causal isolate - Chao-fan Zhang; Cui-Ping Song; Chang-mu Chen; Shang-jin Cui; Lan-fei Miao (Tropical Animal Health and Production, 2010)

Triaxial ellipsoid models of the Moon based on the laser altimetry data of Chang’E-1 - WenRui Wang; Fei Li; JianJun Liu; Xin Ren; XiaoDuan Zou; LingLi Mu; JianGuo Yan; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Trend and change-point analyses of streamflow and sediment discharge in the Yellow River during 1950–2005 - Peng Gao; Xunchang Zhang; Xinming Mu; Fei Wang; Rui Li; Xiaoping Zhang (Hydrological Sciences Journal, 2010)